DESIGN DEVELOPMENT AND EVALUATION OF BUCCAL TABLET CONTAINING NICORANDIL AS A MODEL DRUG - Biswal, Biswajit; Parmar, Hardik; Nayak, Jyotiranjan (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â Objective: Nicorandil is a vasodilatory drug used to treat angina. Nicorandil has oral bioavailability (70%) and half-life 1 hr. It is administered through the buccal mucosa enters directly in the systemic circulation, thereby minimizing the first pass hepatic metabolism and adverse gastro-intestinal effects. Therefore, the present investigation is concerned with the development of the buccal tablets. Methods: The present work was performed to develop and evaluate buccal tablet containing anti-diabetic drug (nicorandil). Ethyl cellulose was used as backing membrane and carbopol 934p and hydroxypropyl methyl cellulose K100M was used as bucco adhesive polymer. Aspartame was used as a sweetener. Thickness, hardness, weight variation and drug uniformity were investigated. Results: The tablet formulations were also subjected to drug release in 250 ml 6.8 phosphate buffer. Ex vivo bioadhesion, retention time and permeation through porcine buccal mucosa membrane. F5 formulations showed maximum amounts of drugs release (89.24%) at the end of 10 hrs dissolution study. F5 also showed maximum bioadhesion (0.0791 N) and the resident time of F5 formulation was 9.5 hrs. It shows 49.32% drug release after 10 hrs permeation study through porcine buccal mucosa mounted in Franz cell. Conclusion: The results of the study suggested that new buccal tablet formulations of combined bucco adhesive polymers can be suitably developed as an alternate to conventional dosage forms. Keywords: Nicorandil, Buccal tablet, Ex vivo bioadhesion, Ex vivo permeation.